PN-Type Near-Infrared High-Speed Graphene Heterojunction Photodetector - Yun Fang; Qingmin Fu; Yuhang Wei; Jian Liu; Wanchun Yang; Dandan Wang; Xue Zhang (IEEE Photonics Journal, 2025)
In this work, a GaAs-substrate-based PN-type near-infrared high-speed graphene heterojunction photodetector is proposed. The proposed photodetector is only composed of a P-type graphene heterojunction absorption part and a N-type GaAs substrate, where the P-type graphene heterojunction is formed by vertically stacking graphene, InSb, and AlSb layers in a top-down configuration. By precisely tuning the thickness and doping profile of each heterostructure layer, a distinctive graphene heterojunction is developed, which is subsequently utilized to realize an optimized PN-type photodetector exhibiting remarkable photoresponsive behavior. Meanwhile, the photogenerated electrons in the InSb dielectric layer can overcome the interfacial potential energy barrier and inject into graphene, achieving rapid response via ballistic transport in the graphene. Numerical simulations indicate the developed graphene heterojunction photodetector simultaneously attains: (i) a high responsivity of 0.329 A/W, and (ii) ultrafast temporal response, with rise and fall times of 13 ns and 11 ns, respectively.